Overexpression of CXCL17 increases migration and invasion of A549 lung adenocarcinoma cells - Koni, Ekin; Congur, Irem; Tokcaer Keskin, Zeynep (Frontiers in Pharmacology, 2024)
Lung cancer is one of the most frequently diagnosed malignancies and is a widespread disease that affects millions of individuals globally. CXCL17 is a member of the CXC chemokine family that attracts myeloid cells and is associated with the mucosa. CXCL17 can both support and suppress tumor growth in certain types of cancer. A549 LUAD cells were transfected with N-Terminal p3XFLAG-CMV or N-Terminal p3XFLAG-CMV-CXCL17 to establish stably transfected CXCL17-overexpressing cells. Reverse-transcription polymerase chain reaction (RT-PCR) and Enzyme Linked Immunosorbent Assay (ELISA) were performed to verify the levels of CXCL17 mRNA and of CXCL17 protein concentration of stably transfected A549 cells respectively. Wound healing, CCK8, and matrigel invasion assays were performed to assess the effect of CXCL17 overexpression on migration, proliferation, and invasion of A549 cells. When compared to control groups, proliferative capacity of A549 cells were unaffected by CXCL17 overexpression; however, the wound area in the CXCL17 overexpression group had dramatically decreased after 48 h. Similarly, the number of invasion cells was significantly higher in the CXCL17-overexpressing group than in the control ones after 48 h. CXCL17 overexpression significantly increased the ability of A549 cells to migrate and invade, without affecting their proliferative abilities.